Perbezaan Tahap Penglibatan Guru Dalam Membuat Keputusan di Sekolah Menengah di Johor (Kajian Kes : SMK Dato' Mohd Yunos Sulaiman) - Anuar, Sarmin (2004)
The purpose of this study is to identify the different level of teachers’ participation in decision making based on age, gender, educational level, race, religion and teaching experience in Sekolah Menengah Kebangsaan Dato’ Mohd. Yunos Sulaiman, Pekan Nanas, Pontian, Johor. For this research, 46 respondents were selected as study sample. A questionnaire was used as the research instrument. The pilot test showed that reliability of the instrument was 0.9372 on the alpha Cronbach scale. SPSS was used to analyze the data and the result is presented in the form of percentage and mean. T-Test and ANOVA were also used in the data analysis. The finding showed that there was no difference in the level of teachers’ participation in decision making based on age, educational level, race, religion and teaching experience. The result also showed that there was a difference in the level of teachers’ participation in decision making based on gender. Male teachers were found to have higher level of participation in decision making compared to female teachers.